The Clever Body - Csepregi, Gabor (University of Calgary Press, 2006)
In Western civilization, we have come to regard the body as an instrument or a machine that responds to external challenges but does not have a life or creativity of its own. Thanks to some of its inherent capabilities, however, the living body can act in a highly intelligent and creative manner. All of us have noticed from time to time that our body can move naturally, without any conscious effort; it can adapt to new situational demands and propose unexpected solutions. While skiing or rock climbing or sailing, we may have abandoned ourselves to our bodily timing and responsiveness, our acute feeling for new solutions. In The Clever Body, Gabor Csepregi describes in detail the nature and scope of these innate abilities sensibility, spontaneity, mimetic faculty, sense of rhythm, memory, and imagination and reflects on their significance in human life.